A Survey on Scheduling Based Mac Protocol for Congestion Minimization in Internet of Things (IoT) - et. al., Abhijit Biswas, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Recently, in Internet era the most common technology ubiquitous to develop smart environment is Internet of things (IoT) and Wireless Sensor Networks (WSNs).These technologies deployed enormously to formulate wide applications in area of Smart homes, Industrial automation, and security destined applications and information trailing. The huge development in wireless technology is due to great exploration in MEMS concept and Embedded Systems. Huge evolution in this technique leads to access different Medium Access Control (MAC) protocol and this protocol used to access multiple nodes peculiarly in wireless channel. The projected MAC protocol designed to enhance network lifetime. Essentially, the network leads to lot of congestion due to non-availability of IoT equipment and less available resources for various environmental applications. The simulated performance ensures that the conventional algorithm limits their dynamic service quality for IoT based applications. The above setbacks motivate the researches to develop the survey in existing scheduling based MAC protocol by highlighting their parameters.